Traductores, pastores, conversos… ¿jefes? Reflexiones sobre el fundamento evangélico del poder político entre los chacobo (Amazonía boliviana) - Philippe Erikson (Bulletin de l'Institut Français d'Études Andines, 2018)
Although they seem to have converted very few people over the years, since the mid 50’s, Protestant missionaries have played, a crucial role in the political, social and economic lives of the Chacobo of Bolivian Amazon. Recently, their influence seems to have diminished, probably due to less affluent Bolivian missionaries being substituted for North American or Swiss missionaries from the SIL or the Misión Suiza. However, the influence of evangelicals is still quite strong because, among other reasons, most contemporary leadership roles are held by people who have been trained by missionaries and who come from families that have deliberately chosen to take sides with them. Paradoxically, some of the Chacobo who have worked with and/or for the missionaries, for instance as Bible translators or preachers, have nonetheless failed on the local political scene. In spite of their undeniable aptitudes, they simply lacked the other essential ingredient for power: support from influential kinship networks. This paper will therefore reflect on the respective importance of social versus religious determinants on the success of political careers among the Chacobo from 1955 until now.